2019
DOI: 10.1038/s41467-019-08655-7
|View full text |Cite
|
Sign up to set email alerts
|

Globally correlated conformational entropy underlies positive and negative cooperativity in a kinase’s enzymatic cycle

Abstract: Enzymes accelerate the rate of chemical transformations by reducing the activation barriers of uncatalyzed reactions. For signaling enzymes, substrate recognition, binding, and product release are often rate-determining steps in which enthalpy-entropy compensation plays a crucial role. While the nature of enthalpic interactions can be inferred from structural data, the molecular origin and role of entropy in enzyme catalysis remains poorly understood. Using thermocalorimetry, NMR, and MD simulations, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 61 publications
(108 reference statements)
4
44
0
Order By: Relevance
“…Perhaps more importantly, many of these studies have shown how disruptions in these pathways act to change function. Taken with our previous studies, nucleotide/substrate-binding cooperativity emerges as a critical function in protein kinase A that arises from the structural changes of multiple domains (i.e., communities) that must be coordinated and synchronized to ensure a cooperative binding response 18 , 20 . Like other tumorigenic transcriptomes that result in a fully active PKA-C, it is likely that alterations in the allosteric network impart defective binding cooperativity and may play a role in their aberrant functions 35 , 36 , 53 .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Perhaps more importantly, many of these studies have shown how disruptions in these pathways act to change function. Taken with our previous studies, nucleotide/substrate-binding cooperativity emerges as a critical function in protein kinase A that arises from the structural changes of multiple domains (i.e., communities) that must be coordinated and synchronized to ensure a cooperative binding response 18 , 20 . Like other tumorigenic transcriptomes that result in a fully active PKA-C, it is likely that alterations in the allosteric network impart defective binding cooperativity and may play a role in their aberrant functions 35 , 36 , 53 .…”
Section: Discussionsupporting
confidence: 72%
“…3a ). These correlations constitute central allosteric nodes necessary for binding cooperativity 18 , 20 , 31 . In addition, allosteric cross-talk exists between residues in the C-terminal tail and residues in the αA-helix (K21, K28), αE-helix (R144, A147, L152), activation loop (R190, V191, G193), and αF-helix (G214, G225).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the physiological substrate PLN in complex with PKA exhibits a committed open-close conformational landscape, with little of the tertiary or higher-order substates observed in the PKS complex. This result agrees well with the synchronous global process measurable by NMR relaxation dispersion only for PKA:PLN but not for PKA:PKS (56). The observed free-energy landscape of the PKA:PLN complex most resembles the PKA:RIIβ complex, highlighting that both substrates are native phospho-acceptor sequences.…”
Section: Dynamic Signatures Of the Kinase:nucleotide:inhibitor Ternarysupporting
confidence: 86%
“…Thus, there is a need to perform studies that addresses the internal motions for both binding partners. Furthermore, many of the previously published NMR ps-ns dynamics studies on protein binding have mostly focused on backbone motions, but it has been demonstrated that it is crucial to also investigate side chain dynamics, which can correspond to substantial conformational entropy, are heterogeneous, are involved in allosteric phenomena, and can have a significant response upon binding 1,4,6,11,26,27 . However, studies in which the side chain fast dynamics have been investigated remain a minority among the experimental studies on protein dynamics by NMR.
Figure 1The 3D structure of the TAZ1/CTAD-HIF-1α complex 16 (pdb code 1L8C).
…”
Section: Introductionmentioning
confidence: 99%